2015
DOI: 10.18632/oncotarget.5588
|View full text |Cite
|
Sign up to set email alerts
|

CD19+CD24hiCD38hiBregs involved in downregulate helper T cells and upregulate regulatory T cells in gastric cancer

Abstract: Regulatory B cells (Bregs) play a critical role in inflammation and autoimmune disease. We characterized the role of Bregs in the progression of gastric cancer. We detected an increase in Bregs producing IL-10 both in peripheral blood mononuclear cells (PBMCs) and in gastric tumors. Multicolor flow cytometry analysis revealed that a subset of CD19+CD24hiCD38hi B cells produces IL-10. Functional studies indicated that increased Bregs do not inhibit the proliferation of CD3+T cells or CD4+ helper T cells (Th cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 53 publications
4
95
0
Order By: Relevance
“…In human PBMCs, we identified naïve B cells (CD19 + CD27 − ) and to a lesser extent transitional (CD19 + CD24 hi CD38 hi ) and memory B cells (CD19 + CD27 + ) as IL‐10‐producing target cells for CpG+IFN‐γ stimulation, while plasma B cells (CD19 + CD24 − CD38 hi ) were not responsive. Our results are in line with previous reports, which showed that CD27 − B cells (corresponding to naïve B cells), transitional B cells, CD24 hi CD27 + (overlapping with the phenotype of memory B cells) and CD73 − CD25 + CD71 + B cells can all produce IL‐10 . Apparently, no clearcut phenotypic markers can be used to characterize IL‐10‐producing B cells.…”
Section: Discussionsupporting
confidence: 91%
“…In human PBMCs, we identified naïve B cells (CD19 + CD27 − ) and to a lesser extent transitional (CD19 + CD24 hi CD38 hi ) and memory B cells (CD19 + CD27 + ) as IL‐10‐producing target cells for CpG+IFN‐γ stimulation, while plasma B cells (CD19 + CD24 − CD38 hi ) were not responsive. Our results are in line with previous reports, which showed that CD27 − B cells (corresponding to naïve B cells), transitional B cells, CD24 hi CD27 + (overlapping with the phenotype of memory B cells) and CD73 − CD25 + CD71 + B cells can all produce IL‐10 . Apparently, no clearcut phenotypic markers can be used to characterize IL‐10‐producing B cells.…”
Section: Discussionsupporting
confidence: 91%
“…FoxP3 ? T cells in a TGF-b dependent way in gastric cancer patients and concluded that CD19 ?-CD24 hi CD38 hi cells involve in gastric cancer immune scape [22]. In our study a significant correlation was found between serum TGF-b and Tregs which suggests that the increase in circulating Tregs may be TGF-b dependent in breast cancer patients.…”
Section: Discussionsupporting
confidence: 55%
“…effector T cells, including cytokines such as TGF-b and IL-10 [33]. Bregs are also capable of directly inducing anergy of Th1 cells, CD8, and CD4 T cells [34] or indirectly by converting Tregs [19,22]. Some studies indicated that the Tregs immunosuppressive role in tumors is mediated by Bregs [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In gastric cancer, Wang et al . described a subset of Bregs with a phenotype (CD19 + CD24 hi CD38 hi ) conversion of effector T cells into CD4 + FoxP3 + Tregs via TGF‐β1 . However, another study demonstrated that CD19 + CD24 hi CD38 hi B cells of healthy individuals repress the proliferation of CD4 + CD25 − T cells and decrease the production of IFN‐γ and tumor necrosis factor‐α by these cells, in part, by producing IL‐10.…”
Section: Dual Aspects Of the Biological Function Of B Cellsmentioning
confidence: 99%